2014
DOI: 10.1186/1471-2202-15-2
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory, mitochondrial, and histological changes following cerebral ischemia in swine

Abstract: BackgroundIschemic brain injury due to stroke and/or cardiac arrest is a major health issue in modern society requiring urgent development of new effective therapies. The aim of this study was to evaluate mitochondrial, microcirculatory, and histological changes in a swine model of global cerebral ischemia.ResultsIn our model, significant microcirculatory changes, but only negligible histological cell alterations, were observed 3 h after bilateral carotid occlusion, and were more pronounced if the vascular occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
1
16
0
2
Order By: Relevance
“…While neurological deficits were clearly evident in the ischemic group in our study, the histologic changes were less obvious. In fact, a study that confirmed our findings reported insignificant neuronal death despite reduced mitochondrial oxidative phosphorylation and microcirculation after global ischemia induced by 3-hour BCCAO occlusion (22). Fortunately, we evaluated cell death with TUNEL and detected apoptotic cells.…”
Section: █ Conclusionsupporting
confidence: 82%
“…While neurological deficits were clearly evident in the ischemic group in our study, the histologic changes were less obvious. In fact, a study that confirmed our findings reported insignificant neuronal death despite reduced mitochondrial oxidative phosphorylation and microcirculation after global ischemia induced by 3-hour BCCAO occlusion (22). Fortunately, we evaluated cell death with TUNEL and detected apoptotic cells.…”
Section: █ Conclusionsupporting
confidence: 82%
“…Complex I-driven respiratory dysfunction is a persistent characteristic of early mitochondrial dysfunction within 6–8 h following traumatic and ischemic injury in the brain, and even in other organ systems such as the heart (Almeida et al, 1995; Gilmer et al, 2009; Kunz et al, 2000; Lemieux et al, 2011; Niatsetskaya et al, 2012; Robertson, 2004; Singh et al, 2006; Suchadolskiene et al, 2014). Previous studies in focal TBI, in both mature and immature rodents, have shown a recovery of complex I-driven respiration to sham levels by 24 h post-CCI in the ipsilateral brain, an observation that differs from those in our study (Kilbaugh et al, 2011; Singh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…На осно-ве этой модели изучены последствия острого кратко-временного прекращения кровообращения в головном мозге, особенности поведенческих реакций и невроло-гических расстройств животных в ранний и поздний вос-становительный период, а также эффекты длительной гипоксии (более 8 мин) [18]. Несколько позднее техни-ка накладывания манжеты на шею с модификациями (артериальная гипотензия) использовалась на приматах [19] и свиньях [20]. В целом эта модель лучше всего подходит для изучения особенностей нарушения кро-вообращения в гиппокампе и стволе головного мозга.…”
Section: модели полной глобальной церебральной ишемииunclassified
“…Двухсосудистая окклюзия с гипотензией оптималь-но подходит для изучения последствий перенесенной гипоксии-ишемии, эффекта реперфузии, особенностей восстановительного периода. С использованием этой модели изучены особенности фосфолипидного и энерге-тического метаболизма, действия нейротрансмиттеров, морфологические изменения вследствие ишемии, влия-ние различных температурных режимов на исходы пери-натального гипоксически-ишемического поражения ЦНС [20,56]. Сложность определяется необходимостью точного контроля системного артериального давления, длительности ишемии, температуры тела, использова-ния определенного режима анестезии, а также над-лежащего послеоперационного ухода.…”
Section: остановка сердца (фибрилляция желудочков)unclassified